2021
DOI: 10.1007/s10649-021-10072-x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching mathematics with technology: a multidimensional analysis of teacher beliefs

Abstract: Teacher self-efficacy beliefs, epistemological beliefs, and beliefs about teaching with technology are regarded as crucial factors for teaching mathematics with technology. However, there is a lack of research that investigates these beliefs while taking into account the multidimensionality of the constructs. In this cross-sectional study with n = 198 upper secondary in-service teachers in Germany, we used multidimensional scales to measure teachers’ i) beliefs about teaching with technology, ii) self-efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 72 publications
2
25
0
Order By: Relevance
“…However, there are also beliefs that can be classified as neutral, related to general issues; for example, beliefs about timing, such as at what point in a lesson a teacher should use digital tools [41,43]. Another dimension of teachers' beliefs regarding digital tools is self-efficacy beliefs [44]. Thurm and Barzel [44] found that self-efficacy for designing lessons with digital tools (also for technical implementation) is an important factor when using digital tools in the classroom.…”
Section: Teachers' Beliefs About Digital Toolsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there are also beliefs that can be classified as neutral, related to general issues; for example, beliefs about timing, such as at what point in a lesson a teacher should use digital tools [41,43]. Another dimension of teachers' beliefs regarding digital tools is self-efficacy beliefs [44]. Thurm and Barzel [44] found that self-efficacy for designing lessons with digital tools (also for technical implementation) is an important factor when using digital tools in the classroom.…”
Section: Teachers' Beliefs About Digital Toolsmentioning
confidence: 99%
“…Another dimension of teachers' beliefs regarding digital tools is self-efficacy beliefs [44]. Thurm and Barzel [44] found that self-efficacy for designing lessons with digital tools (also for technical implementation) is an important factor when using digital tools in the classroom. As a result, within the teacher education program, there should be "a stronger focus on allowing teachers to gain specific mastery experience in implementing technology as this is the most powerful source of teachers self-efficacy" ( [44], p. 58).…”
Section: Teachers' Beliefs About Digital Toolsmentioning
confidence: 99%
See 3 more Smart Citations